FACTORS INFLUENCE THE ACQUISITION OF VOCABULARY BY YOUNG LEARNERS - Andari, Ida Ayu Made Yuni (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2023)
This research focuses on the factors that influence vocabulary acquisition by young learners. This study analyses how internal and external factors influence vocabulary or language acquisition. A person's abilities are influenced by various factors that exist in individuals and the environment, as well as vocabulary abilities. In learning and having adequate vocabulary skills, it is also influenced by several factors that must be considered so that these vocabulary abilities also help students' language and speech development. The data in this study were ten students at Horray School. The data collection technique for this research used observation and questionnaire methods. In this case, observations were made for three weeks, and then a post-test was given to students at the last meeting every week. There is also a questionnaire to be distributed and filled in by parents of students to obtain information on the factors influencing students in mastering English or vocabulary. This study's results indicate several factors that influence students' vocabulary mastery. There are three internal factors: age, experience, and learning style. The three external factors are motivation, instruction, and access to native speakers. These factors come from within the individual or internal and in the environment or external. The environment, in this case, also influences children's vocabulary skills because it is a place for children to adapt and develop their abilities, skills and understanding of various things, including vocabulary mastery.